The correlation of caregiving burden with depression, anxiety, and stress among caregivers of people with schizophrenia - I Kadek Suaryana; Cokorda Bagus Jaya Lesmana; Luh Nyoman Alit Aryani (Indoscholar Publication and the Indonesian Psychiatric Association, 2020)
Background: Schizophrenia is a severe mental disorder that requires collaborative approach from the health care provider, family, and the society in its management. Adequate support from the family of people with schizophrenia plays a significant role in their recovery. However, providing support to these patients might become a significant burden among caregiver that it might induce the occurrence of stress, mood changes, and anxiety. This research aimed to determine the correlation between caregiver burden and the mental problems that might be experienced by caregivers of people with schizophrenia.Patients and Methods: This qualitative research employed a cross-sectional analytic design. Samples were obtained consecutively in June and July 2018. The questionnaires used were the 22 item Zarit Burden Interview (ZBI) and the 42 item Depression, Anxiety and Stress Scale (DASS-42).Results: A number of 69 subjects participated. The caregiving burden demonstrated strong positive significantly correlations with problems including depression, anxiety, and stress (r=0,618, r=0,694, r=0,808, respectively ; all p<0.001). Conclusion: There is a relationship between caregiving burden and depression, anxiety, and stress on caregivers of people with schizophrenia (PWS) in Sanglah Hospital in Denpasar.